2019
DOI: 10.18805/ijar.b-995
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and dry matter digestibility in sheep fed first and second cut reed canary grass (Phalaris arundinacea L.)

Abstract: We investigated the intake and digestibility of different reed canarygrass (RCG) growth stages by sheep. RCG was cultivated in an experimental field and harvested at the first and second cuts at each pre-blooming stage. Feeding behavior was monitored on adult female sheep, fed 3 kg each of fresh RCG three times daily. While the crude protein content and dry matter digestibility of RCG were significantly higher in leaf than in stem tissue of both first and second cut in harvesting times, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Previous study has illustrated that RCG silage produced using glucose, formic acid, and tannic acid could change the fermentation characteristics with reduction of acetic acid and ammonia-N (Tokita et al, 2015). However, the effects of biological additives on RCG silage fermentation remained unclear.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has illustrated that RCG silage produced using glucose, formic acid, and tannic acid could change the fermentation characteristics with reduction of acetic acid and ammonia-N (Tokita et al, 2015). However, the effects of biological additives on RCG silage fermentation remained unclear.…”
Section: Ta B L Ementioning
confidence: 99%
“…Previous studies have also shown that inoculants with a mixture of LAB and cellulase resulted in a considerable improvement in silage quality (Hou, Gentu, Jia, & Cai, 2017; Khota, Pholsen, Higgs, & Cai, 2016; Meeske, Basson, & Cruywagen, 1999; Sun et al, 2012). Although studies have reported the fermentation characteristics of RCG silage in the USA (Cherney, Alessi, & Cherney, 2006; Kammes et al, 2008), Canada (Bélanger et al, 2016), and Japan (Tokita et al, 2015), there is little information on the fermentation characteristics of inoculated RCG silage on the Qinghai‐Tibetan Plateau with inherently extreme and unstable climate.…”
Section: Introductionmentioning
confidence: 99%